1999
DOI: 10.1111/j.1600-0714.1999.tb02052.x
|View full text |Cite
|
Sign up to set email alerts
|

Burning mouth syndrome: prevalence and associated factors

Abstract: Burning mouth syndrome (BMS) is characterized by a burning sensation in the oral cavity although the oral mucosa is clinically normal. The syndrome mostly affects middle‐aged women. Various local, systemic and psychological factors have been found to be associated with BMS, but its etiology is not fully understood. Oral complaints and salivary flow were surveyed in 669 men and 758 women randomly selected from 48,500 individuals between the ages 20 and 69 years. Fifty‐three individuals (3.7%), 11 men (1.6%) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
307
1
28

Year Published

2000
2000
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 374 publications
(358 citation statements)
references
References 26 publications
22
307
1
28
Order By: Relevance
“…However, the present study failed to demonstrate a statistical correlation between the characteristics of physical pain and the psychological status. Our findings suggest that anxiety and depression are independent of the intensity of BMS (4,31). Therefore, it remains unclear whether psychiatric disorders are a cause or consequence of iBMS.…”
Section: Psychological Statusmentioning
confidence: 66%
See 2 more Smart Citations
“…However, the present study failed to demonstrate a statistical correlation between the characteristics of physical pain and the psychological status. Our findings suggest that anxiety and depression are independent of the intensity of BMS (4,31). Therefore, it remains unclear whether psychiatric disorders are a cause or consequence of iBMS.…”
Section: Psychological Statusmentioning
confidence: 66%
“…The prolonged pain, comorbidities, and unsuccessful treatments associated with iBMS can affect one's mood (11,(15)(16)(17), induce or reinforce psychiatric disorders such as anxiety, depression, and cancerophobia (4,7,(18)(19)(20), and impair one's quality of life (10,11,(21)(22)(23). It is important to determine how the oral symptoms of iBMS impact the daily life of patients.…”
Section: Originalmentioning
confidence: 99%
See 1 more Smart Citation
“…There is no precise information on the clinical course and prognosis of BMS. Improvement has been cited in one-half to two-thirds of patients within 6-7 years of onset, with spontaneous remission rates of 20% in that time frame [76,79]. One clinical study found spontaneous remission to occur in 3% of patients within 5 years after diagnosis [76,80].…”
Section: Burning Mouth Syndromementioning
confidence: 99%
“…Synonyms found in literature include glossodynia, oral dysesthesia, glossopyrosis, glossalgia, stomatopyrosis, and stomatodynia [1][2][3][4] . It usually affects women aged between 40 and 60 years and the prevalence in the general population is 3.7% (1.6% men and 5.5% women) 5 .…”
Section: Introductionmentioning
confidence: 99%